Illegal Access dalam Pemanfaatan Mangrove untuk Arang Bakau oleh Masyarakat di Batu Ampar, Kalimantan Barat - Rita Bulan; Sambas Basuni; Nyoto Santoso; M. Bismark (Jurnal Hutan dan Masyarakat, 2019)
This study aims to identify the causes of illegal access for the community in carrying out mangrove utilization activities as raw material for charcoal in Batu Ampar District, Kubu Raya, West Kalimantan. This research was conducted in 3 villages in Batu Ampar Subdistrict, namely Batu Ampar Village, Nipah Panjang Village and Teluk Nibung Village. Data collection was done through field observations, in-depth interviews, documentation studies and literature studies. Data analysis used descriptive analysis method with the Theory of Access approach according to Ribot and Peluso (2003). The results showed that the causes of illegal access in the use of mangroves as a raw material for charcoal by the community in Batu Ampar Subdistrict were the characteristics of protected forest resources as Common Pool Resources (CPRs) and high exclusion costs and the obmission of local government. The communities get the power of access to protected forests in Batu Ampar mainly through access to capital provided by investors (cukong), both collectors and buyers.